ANTIOXIDANT PROPERTIES OF SOLID DISPERSED SYSTEM OF HESPERIDIN OBTAINED BY CENTRIFUGAL FIBER FORMATION - ЛІСОВИЙ, В. М.; БЕССАРАБОВ, В. І. (Technologies and Engineering, 2024)
Purpose. Development and study of the effect of polymeric solid dispersed system (SDS) of hesperidin on the processes of protein and lipid peroxidation. Methodology. A highly soluble solid dispersed system of hesperidin was obtained by means of an innovative technology of centrifugal fiber formation using a commercially available cotton candy machine. The effect of centrifugally formed SDS of hesperidin on lipid peroxidation (LPO) was evaluated by the method of determining the amount of products that react with thiobarbituric acid (TBA). This method is indirect and is based on the ability of TBA to interact with malondialdehyde (MDA), which is the end product of oxidative lipid degradation and an intermediate product of the enzymatic oxidation of peanut donic acid. The study of the effect of hesperidin SDS on the process of protein peroxidation (PPO) was carried out by determining the level of optical density of dinitrophenylhydrazones, the final reaction products formed during the interaction of oxidized amino acid residues of proteins with 2,4-dinitrophenylhydrazine (2,4-DNPH). Findings. A highly soluble polymeric solid dispersed system of hesperidin was developed by the method of centrifugal fiber formation. It has been proved that the use of the obtained SDS of hesperidin leads to a decrease in the amount of lipid and protein peroxidation products. At the same time, the inhibitory effect in the studied systems improves with increasing concentration of SDS of hesperidin, indicating a concentration-dependent antioxidant effect. Originality. For the first time, it was established that the highly soluble solid dispersed system of hesperidin, obtained by the method of centrifugal fiber formation, effectively inhibits the process of peroxidation of proteins and lipids in a dose-dependent manner. Practical value. The highly soluble solid dispersed system of hesperidin can be used as an active pharmaceutical ingredient (API) for the development of drugs with antioxidant properties for the treatment and prevention of neurodegenerative diseases.